2008
DOI: 10.3349/ymj.2008.49.3.383
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Parecoxib and Proparacetamol in Endoscopic Nasal Surgery Patients

Abstract: PurposeThe aim of the study was to compare the efficacy of parecoxib for postoperative analgesia after endoscopic turbinate and sinus surgery with the prodrug of acetaminophen, proparacetamol.Materials and MethodsFifty American Society of Anesthesiology (ASA) physical status I-II patients, receiving functional endoscopic sinus surgery (FESS) and endoscopic turbinectomy, were investigated in a prospective, randomized, double-blind manner. After local infiltration with 1% mepivacaine, patients were randomly allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 22 publications
0
26
0
1
Order By: Relevance
“…This is an expected finding [9][10][11][12][13][14][15] and adds to the capacity of the PQRS to discriminate between surgical procedures. We also found an effect on ADL and in overall recovery, which would be consistent with the differences between groups in pain and nausea.…”
Section: Discussionmentioning
confidence: 79%
“…This is an expected finding [9][10][11][12][13][14][15] and adds to the capacity of the PQRS to discriminate between surgical procedures. We also found an effect on ADL and in overall recovery, which would be consistent with the differences between groups in pain and nausea.…”
Section: Discussionmentioning
confidence: 79%
“…[13,14] Fonksiyonel sinüs cerrahisinde (FESC) ameliyat sonrası ağrı kontrolü aralıklarla uygulanan nonopioid analjeziklere dayanmaktadır. [15][16][17][18] Çalışma-mızda, non-opoid ilaçlar grubunda yer alan diklofenak sodyumu tercih ettik ve ameliyat sonrası 24 saatlik diklofenak ihtiyacının plasebo grubunda en çok ve gabapentin grubunda en az olduğunu göz-lemledik.…”
Section: Discussionunclassified
“…The activation of PAR-2 up-regulates COX expression, 41,42 which is crucial for PAR-2-medaited hyperalgesia. 9,43 While morphine promotes COX-1 gene expression in a rat microglial cell line in a dosedependent manner, [44][45][46] COX inhibitors can effectively reduce pain and morphine requirements in managing postoperative acute pain. [45][46][47][48][49] We found that treatment with a small dose of PAR-2 antagonist enhanced the antinociceptive effect of morphine.…”
Section: Interaction Of Fsllry-nh2 With Morphinementioning
confidence: 99%